Tear and blood salusin-?, and -?, copeptin, and asprosin in patients with glaucoma and ocular hypertension - Arslan, Sermal; Kaya, Mehmet Kaan; Aydin, Suleyman (Consel Brasil Oftalmologia, 2025)
Purpose: This pilot study was conducted to investigate the presence of various bioactive compounds (copeptin, asprosin, and salusins) in the blood and tears of patients with glaucoma. Methods: A total of 83 subjects, including 28 patients with open-angle glaucoma, 28 patients with ocular hypertension, and 27 control volunteers, were enrolled in this study. The levels of salusin-alpha, salusin-(3, copeptin, and asprosin in tears and venous blood samples were measured by enzyme linked immunosorbent assay (ELISA). Results: Patients with open-angle glaucoma and those with ocular hypertension showed statistically significantly decreased levels of salusin-alpha and salusin-(3 in their blood and tears compared with those of control subjects (p<0.05), with the decrease being the most pronounced in patients with ocular hypertension (p<0.05). In contrast, the levels of copeptin and asprosin showed a statistically significant increase in both these patient groups compared with those of control subjects (p<0.05). There was a negative correlation between intraocular pressure and blood and tear salusins. Conclusions: Fluids from patients with open-angle glaucoma and ocular hypertension showed lower salusin levels. Patients with ocular hypertension had higher levels of copeptin and asprosin, but not those with open-angle glaucoma (except for asprosin, whose levels showed a slight but remarkable increase in plasma in patients with open-angle glaucoma). The pathogenesis of ocular hypertension and open-angle glaucoma may be significantly impacted by these biomarkers.
Keywords: Glaucoma; open-angle/physiopathology; Intraocular pressure/physiopathology; Retinal ganglion cells/pathology; Biomarkers/blood; Glycopeptides; Fibrillin-1; Tears/chemistry; Intercellular signaling peptides and proteins/blood; Enzyme-linked immunosorbent assay/methods